Penguatan Pengelolaan Lingkungan dan Pemberdayaan Masyarakat di Kelurahan Sawah Lebar - Antonius, Antonius; Hamid, Rita; Wahyuni, Liza; Trigono, Rahmad; Guswandi, Yongki; Kencana , Bayu Surya; Karmanita , Deti; Aprianto , Sandi (Jurnal Kewirausahaan dan Bisnis, 2026)
Environmental and social issues, particularly household waste management, remain major challenges in urban residential areas. Low levels of collective community awareness, limited facilities, and the underutilization of the economic potential of waste have adversely affected environmental quality and public health. This community service article aims to describe and analyze the implementation of the Thematic Community Service Program (KKNT) of Dehasen University Bengkulu in RT 27 RW 06, Sawah Lebar Subdistrict. The method employed was a participatory descriptive approach through observation, direct action, and activity documentation. The results indicate an increase in community awareness of environmental cleanliness, strengthened mutual cooperation, and an initial understanding of waste banks as an alternative economic potential. This program contributes positively to supporting sustainable, environment-based community development.